Socio-political processes in Greek villages of Mariupol region оf People’s Republic of Ukraine at the period Сentral Rada - Volodymyr Romantsov (Cхід, 2013)
The article deals with the socio-political processes in Greek villages of Northern Azov region that happened in UNR at the period ofCentral Rada. The author identifies the problem of political struggle which took place among Greek-peasants at the boundary of 1917-1918. The questions of national cultural revival, the problems of agrarian relations in Greek villages community are highlighted.